Meta‐analysis of the association between primary tumour location and prognosis after surgical resection of colorectal liver metastases. Issue 13 (6th August 2019) - Wang, X.‐Y.; Zhang, R.; Wang, Z.; Geng, Y.; Lin, J.; Ma, K.; Zuo, J.‐L.; Lu, L.; Zhang, J.‐B.; Zhu, W.‐W.; Chen, J.‐H.
Abstract : Background: Primary tumour location is emerging as an important prognostic factor in localized and metastatic colorectal cancers. However, its prognostic role in colorectal liver metastasis (CRLM) after hepatectomy remains controversial. A systematic review and meta‐analysis was undertaken to evaluate its prognostic value. Methods: References were identified through searches of PubMed, Embase, Web of Science and the Cochrane Library comparing overall or disease‐free survival after hepatic resection between patients with CRLM originating from right‐ or left‐sided colorectal cancers. Data were pooled using hazard ratios (HRs) and 95 per cent confidence intervals according to a random‐effects model. Meta‐regression and subgroup analyses were conducted to assess the effect of underlying confounding factors on HR estimates and to adjust for this. Results: The final analysis included 21 953 patients from 45 study cohorts. Compared with left‐sided primary tumour location, right‐sided location was associated with worse overall survival (HR 1·39, 95 per cent c.i. 1·28 to 1·51; P  < 0·001; prediction interval 1·00 to 1·93), and also tended to have a negative impact on disease‐free survival (HR 1·18, 1·06 to 1·32; P  = 0·004; prediction interval 0·79 to 1·75). Subgroup analysis showed that the negative effect of right‐sided primary tumour location on overall survival was more prominent in the non‐Asian population (HR 1·47, 1·33 to 1·62) than the Asian population (HR 1·18, 1·05 to 1·32) ( P for interaction <0·01). Conclusion: This study demonstrated a prognostic role for primary tumour location in patients with CRLM receiving hepatectomy, especially regarding overall survival. Adding primary tumour location may provide important optimization of prognosis prediction models for CRLM in current use. Abstract : The prognostic role of primary tumour location in colorectal liver metastases (CRLM) after hepatectomy remains controversial. This meta‐analysis demonstrated a prognostic role of primary tumour location in CRLM receiving hepatectomy, especially regarding overall survival. Primary tumor location has prognostic value Abstract : Antecedentes: La ubicación del tumor primario ( primary tumor loca tion, PTL) ha surgido como un factor pronóstico importante en los cánceres colorrectales ( colorectal cancers, CRCs) localizados y metastásicos. Sin embargo, todavía se discute su relevancia como factor pronóstico tras la resección de metástasis hepáticas de cáncer colorrectal ( colorectal liver metastases, CRLM). Se realizó una revisión sistemática y un metaanálisis para determinar su valor pronóstico. Métodos: En PubMed, EMBASE, Web of Science y la Biblioteca Cochrane se identificaron los trabajos que compararon la supervivencia global ( overall survival, OS) y la supervivencia libre de enfermedad ( disease‐free survival, DFS) tras la resección hepática de CRLM cuyo CRCs estuviese situado en el lado derecho o izquierdo. Los datos se expresaron en forma del cociente de riesgos instantáneos ( hazard ratio, HR) e intervalos de confianza del 95% (i.c. del 95%) de acuerdo con un modelo de efectos aleatorios. Se efectuaron análisis de metarregresión y de subgrupos para evaluar el efecto de los factors de confusión existentes en las estimaciones de HR, ajustando por los mismos. Resultados: El análisis final incluyó 21.953 pacientes de cohortes de 45 estudios. La PTL en el lado derecho en comparación con el lado izquierdo se asoció con una peor supervivencia global (HR 1, 39; i.c. del 95% 1, 28‐1, 51; P < 0, 001; intervalo de predicción 1, 00‐1, 93) y una tendencia a un impacto negativo en la DFS (HR 1, 18; i.c. del 95% 1, 06‐1, 32; P = 0, 004; intervalo de predicción 0, 79‐1, 75). El análisis de subgrupos mostró que el efecto negativo de la PTL del lado derecho en la OS fue más prominente en la población no asiática (HR 1, 47; i.c. del 95% 1, 33‐1, 62) que en la asiática (HR 1, 18; i.c. del 95% 1, 05‐1, 32; P interacción < 0, 01). Conclusión: Este estudio demostró que la PTL tiene un papel pronóstico tras la hepatectomía de las CRLM, especialmente respecto a la OS. La adición de la PTL proporcionaría una optimización importante en los modelos actuales de predicción pronóstica de CRLM.